64 × 48 TOF sensor in 0.35 µm CMOS with high ambient light immunity. Issue 19 (1st September 2014) - Davidovic, M.; Seiter, J.; Hofbauer, M.; Gaberl, W.; Schidl, S.; Zimmermann, H.
Abstract : A multi‐pixel 64 × 48 time‐of‐flight (TOF) range sensor whose speciality is high immunity against ambient light is presented. The chip was fabricated in a 0.35 µm 1P4M CMOS process, whereby a single pixel occupies an area of 45 × 60 µm 2 achieving a fill factor of 50%. The measured distance shows a 1 σ deviation below 3.7 mm in the optimum operating range for the sensor. The measurement results show that the sensor successfully acquires the distance even when some parts of the scenery are illuminated with 180 klx ambient light. Furthermore, the most accurate method to characterise particular pixels in a multi‐pixel array is for the first time used in a multi‐pixel TOF sensor.